An Econometric Evaluation of the Effects of the Canada-United States Automobile Agreement of the Canadian Automotive Manufacturing Industry - D.A. Wilton (Queen's University, Department of Economics, 1972)
The purpose of ths paper is to present a set of estimates designed to measure the economic impact of the Agreement on the Canadian automotive manufacturing industry. This modest objective not only totally ignores the impact of the agreement on the United States industry, it also ignoresthe impact on the rest of the Canadian economy. In other words, this partial equilibrium analysis of the effects of the Agreement on one particular industry fails to consider the effects of the myriad of small to medium sized firms engaged in the production of parts and accessories, the effects on other input-output connected industries, and the usual multiplier effects on the economy.
Keywords: 330